Krümmungs- und Torsionstensoren des Raumes von Zentralpunktoren - Maziliauskaitė, S. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:С. Мазиляускайте, Тензоры кручения и кривизны пространства центральных пункторовS. Maziliauskaitė, Centrinių punktorių erdvės sukimosi ir kreivumo tenzoriai